การศึกษาเภสัชจลนศาสตร์ของยามัยโคฟีโนเลตโมฟีติลในผู้ป่วยปลูกถ่ายไตชาวไทย - วิเชียร จุฬาเสรีกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
BACKGROUND: MMF which is a prodrug of an immunosuppressive drug, mycophenolic acid (MPA), has been effectively used in kidney transplantation. The suggested dose of MMF in the Western KT patients is 2 gm/d. Because of the gastrointestinal side effects of MMF at such dose, several Thai KT patients usually obtain MMF at the lower dose, 1-1.5 gm/d. No pharmacokinetic data of MMF is available in Thailand. OBJECTIVE: To study was performed in 19 Thai KT patients with stable renal function After an overnight fasting, a single oral dose of 500 mg MMF was given. Plasma concentrations of MPA, determined by high-performance liquid chromatography (HPLC), were measured at the time of 0 (predose) to 12 hours after drug administration. A complete area under the concentration time curve (AUC) from 0 to 12 hours, AUC 0-12hr-1 was calculated by using the trapezoidal rule. RESULTS: The time to maximal concentration (Tmax) were 1.32 ± 0.82 hr(mean ± SD). The maximal and minimal plasma concentration (Cmax and Ctrough) for MPA were 5.70 ± 1.18 and 2.7 ± 0.29 µg.hr/mL respectively. The values of AUC0-12 hr for MPA were 37.46 ± 3.46 µg.hr/mL. MPA concentration at 8 hrs after dosing had the best value of correlation coefficient with the AUC0-12hr (R2 = 0.74, p <0.000). CONCLUSIONS: The pharmacokinetic data including AUC 0-12 hr in Thai KT patients receiving 1 gm/d of MMF are comparable with the KT patients who obtain 2 gm/d of MMF. The MPA concentration at 8 hrs after dosing is the best single alternative indicator of AUC0-12 hr